Co-ordinating local-authority and private-sector planning: A Contribution to regional development at the threshold to the 21st century - Kollatzsch, Jens; Eisold, Tobias (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
This article investigates the opportunities and threats facing co-ordination in planning, as well as theoretical approaches to the explanation of interdependencies between local authorities and the private sector. It also provides the starting point for further research projects in a sphere of action which — under the label “public/private partnerships” — can be expected to gain in importance in the coming years in the field of economic development aid. A systems-theory approach is adopted to show the nature of the relations between the two groups of actors. Building upon this, the authors then attempt to develop explanatory approaches based on regulation theory to illuminate the dynamic relationship which exists between private-sector companies and local authorities. Their findings lend themselves to quantification applying the methods of game theory.
Keywords: Article